An Economic Evaluation of TENS in Addition to Usual Primary Care Management for the Treatment of Tennis Elbow: Results from the TATE Randomized Controlled Trial. - Martyn Lewis; Linda S Chesterton; Julius Sim; Christian D Mallen; Elaine M Hay; Daniëlle A van der Windt (PLoS ONE)
Background The TATE trial was a multicentre pragmatic randomized controlled trial of supplementing primary care management (PCM)-consisting of a GP consultation followed by information and advice on exercises-with transcutaneous electrical nerve stimulation (TENS), to reduce pain intensity in patients with tennis elbow. This paper reports the health economic evaluation. Methods and findings Adults with new diagnosis of tennis elbow were recruited from 38 general practices in the UK, and randomly allocated to PCM (n = 120) or PCM plus TENS (n = 121). Outcomes included reduction in pain intensity and quality-adjusted-life-years (QALYs) based on the EQ5D and SF6D. Two economic perspectives were evaluated: (i) healthcare-inclusive of NHS and private health costs for the tennis elbow; (ii) societal-healthcare costs plus productivity losses through work absenteeism. Mean outcome and cost differences between the groups were evaluated using a multiple imputed dataset as the base case evaluation, with uncertainty represented in cost-effectiveness planes and through probabilistic cost-effectiveness acceptability curves). Incremental healthcare cost was £33 (95%CI -40, 106) and societal cost £65 (95%CI -307, 176) for PCM plus TENS. Mean differences in outcome were: 0.11 (95%CI -0.13, 0.35) for change in pain (0-10 pain scale); -0.015 (95%CI -0.058, 0.029) for QALYEQ5D; 0.007 (95%CI -0.022, 0.035) for QALYSF6D (higher score differences denote greater benefit for PCM plus TENS). The ICER (incremental cost effectiveness ratio) for the main evaluation of mean difference in societal cost (£) relative to mean difference in pain outcome was -582 (95%CI -8666, 8113). However, incremental ICERs show differences in cost-effectiveness of additional TENS, according to the outcome being evaluated. Conclusion Our findings do not provide evidence for or against the cost-effectiveness of TENS as an adjunct to primary care management of tennis elbow.